PERAN KUALITAS PRODUK, HARGA, CITRA MEREK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN: PERAN KUALITAS PRODUK, HARGA, CITRA MEREK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN - Noegroho, Galuh Adrianto; Aprilani, Deddy; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine how much influence product quality, price, brand image, and service quality have on purchasing decisions. The population used is prepaid Telkomsel users in Bandar Lampung. This study used a type of quantitative approach using explanatory. The sampling technique used purposive sampling with non-probability sampling method and the number of samples was 100 respondents. This study uses multiple linear regression analysis techniques with the SPSS 26.0 program. The results of this study indicate that partially the variables of product quality, price, brand image, and service quality have a positive and significant effect on purchasing decisions. The result of the F test in this study incicate variables of product quality, price, brand image, and service quality simultaneously have a significant effect of 69.8% on purchasing decisions. The result of the correlation coefficient research show that the R-square value is 53.4% while the remaining 43.4% is influenced by othet variable not examined in this study, and the R-value obtained in this study is 0.731 and is included in the category of stong relationship level.